Rancang Bangun Sistem Informasi Akademik di Madrasah Ibtidaiyah Al Hidayah Subang dengan Metode Waterfall menggunakan PHP dan MySQL Berbasis Web (Journal Digital Technology Trend, 2023)
In the realm of education, the utilization of web-based academic information systems plays a crucial role in enhancing the efficiency and effectiveness of school management. This research is focused on the design and development of web -based academic information systems for Madrasah Ibtidaiyah Al Hidayah Subang, using the Waterfall methodology with PHP and MySQL technology. This system includes comprehensive features such as student and teacher data management, classroom scheduling, the results of this study are a web -based school academic information system that has features for student data management, teacher data, lesson schedule, test scores and report cards, teacher attendance, and announcements that can provide academic information to users. This academic information system also has good security features to protect school and user data. From the results of testing, the school academic information system that was built can facilitate the management of school data and also facilitate the decision-making process by teachers and administrative staff. This research has several suggestions and can be used as a reference for further research in developing a better web -based academic information system and meeting user needs.